(untitled) (Journal of research in medical and health sciences, 2026)
Against the backdrop of rapid development of medical technology and diversified patient needs, nursing education is facing innovative challenges. Traditional nursing training mainly relies on one-way knowledge transmission and mechanical operation training, which leads to insufficient clinical thinking, self-learning, and adaptability to complex situations among students. Based on the Outcome Based Education (OBE) concept, this study systematically reconstructs the nursing comprehensive skills training course and proposes a modular curriculum design framework guided by core clinical competencies, covering modules such as basic nursing operations, specialized nursing skills, and emergency treatment. Through multiple methods such as situational simulation, layered teaching, and problem-based learning (PBL), students’ clinical decision-making and teamwork abilities are strengthened. A three-dimensional dynamic evaluation system including skill operation, clinical thinking, and professional ethics has been constructed, and a combination of formative evaluation and summative evaluation is adopted to track the development trajectory of students’ abilities in real time.The study verified the effectiveness of the reform through empirical analysis: the experimental group’s students’ skill operation qualification rate increased by 23.6% compared to the traditional teaching group, the excellent rate of clinical thinking assessment increased by 18.4%, and the satisfaction rate of graduates’ job competence reached 92%. Teaching feedback shows that 87.8% of students believe that practical training projects are closer to clinical practice, and 92.1% recognize the teaching value of virtual simulation platforms. Compared with traditional models, the reform curriculum has shown significant advantages in goal setting, innovative methods, and scientific evaluation, effectively shortening students’ clinical adaptation period and improving the efficiency of teaching resource utilization. The study also pointed out that the current reform needs to further optimize the layered teaching strategy, strengthen interdisciplinary scenario simulation training, and establish a dynamic feedback mechanism based on big data. This study provides a replicable practical paradigm for the reform of nursing training courses, emphasizing the need for outcome oriented teaching design to closely connect with clinical needs, and promoting knowledge transfer and ability transformation through diversified teaching methods and evaluation systems. Future research will expand the sample range, explore the application of artificial intelligence and virtual reality technology in skill training, build intelligent and personalized training support systems, and promote the development of nursing education towards precision and sustainability.